Role of the public prosecutor’s office experts in the environmental licensing of the Mexilhão Project, São Paulo, Brazil - Viglio, José Eduardo; Ferreira, Lúcia da Costa (Sustainability in Debate, 2022)
The constitutional role and authority of the Public Prosecutor’s Office (MP) as an enforcer of law warranted the MP protagonism in the enforcement of environmental legislation and accountability of environmental agencies in Brazil. The MP instituted regional offices to tackle the environmental issue and established a team of experts to provide technical support. This research analyzes the participation of the São Paulo State Public Prosecutor’s Office (MPSP) and the Federal Public Prosecutor’s Office (MPF) experts in the environmental licensing of the Mexilhão Project. The project was located in the coastal region of the state of São Paulo and initially aimed to reduce by half the volume of natural gas imported by the country. Based on the analysis of documents and interviews, this paper shows that there were different interpretations and framings among the MP experts concerning environmental impacts and risks of the project. This study also discusses MP's influence on the decisions of the federal environmental agency about the Mexilhão Project.